Detection of Staphylococcus aureus from contact surfaces of public buses in Bangkok and metropolitan area, Thailand - NARUMON BOONMAN; JARUWAN CHUTRTONG; CHANATE WANNA; SIRIPHAN BOONSILP; SUPATRA CHUNCHOB (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Boonman N, Chutrtong J, Wanna C, Boonsilp S, Chunchob S. 2022. Detection of Staphylococcus aureus from contact surfaces of public buses in Bangkok and metropolitan area, Thailand. Biodiversitas 23: 3395-3400. The purpose of present investigation was to determine the prevalence of different species of genus Staphylococcus on the contact surfaces of public buses in Bangkok and metropolitan area. A total of 180 samples were collected from handrails, seats, and window frames of each bus of 2 bus terminals, Bangkhen and Morchit, divided into 15 non-air-conditioned buses and 15 air-conditioned buses from each terminal. The samples were cultivated and identified by Gram’s stain and biochemical tests. The results showed that 76.7% from Bangkhen and 80% from Mochit were contaminated with Staphylococcus spp. Based on the type of vehicles, Staphylococcus spp. was found in 93.3% of air-conditioned buses and 63.3% of non-air-conditioned buses. Considering the sampling location, Staphylococcus spp. was found in 28.3% of handrails, 50% of seats and 51.7% of window frames. Four isolates of Staphylococcus aureus were discovered among 294 isolates in a total of Staphylococcus spp., including 3 isolates from Bangkhen and 1 isolate from Mochit. Only one isolate was contaminated on the non-air-conditioned bus, whereas 3 isolates were on the air-conditioned buses. Two isolates of them were found from seats and 2 isolates from window frames. Disk diffusion susceptibility test showed that 3 isolates of S. aureus resisted fusidic acid and fosfomycin. The results suggested that Staphylococcus spp. and S. aureus were prevalence in public transport systems which were a source of infection to the persons. Therefore, effectively controlling their distribution is necessary to reduce the risk of bacterial infections in public bus users.